Peranan Wanita dalam Islam dan Feminisme Barat - Hamidah Hanim Midah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The purpose of this study is to determine the role and rights of women in Islamic and Western views. Islam is a grace to all nature and although we know that women are created from male ribs, Islam never states that women’s degrees are below men. The methodology used literature studies. As for the research results that the role of women is said to be important because of the many heavy loads it has to deal with, even the burdens that men should have been imposing. Women have equal and equal rights in Islam in contrast to those prosecuted by Western women who demand equality and identification between men and women in every respect. The point of departure they use in this is that their rights must be equal, identical and comparable. There is no privilege and primacy for either of them. Equations are different from those of the identities. The gender equations many westerners had buzzed, evidently having permeated into the body of these Muslims' Muslims. They had been fooled by the thoughts of the westerners, not even a few of whom were to screech the thought. Natural law is fixed in nature to have regulated gender relations in society. So, when in society there is and there is a female subordination phenomenon, it is due to female biological factors. Some answers about the low role of public dissector women due to biological constraints, such as menstruation, pregnancy, childbirth, and breastfeeding. All of them became women's inhibitors to play a significant role in society.